Market Meltdown and the Propagation Mechanism of Contagion - Dilip K., Ghosh; Dipasri, Ghosh (Universiti Utara Malaysia, 2010)
World economy came on a tailspin because of market meltdown and the propagation of contagion triggered by recession, starting mostly from the US economy. This work highlights the grim developments in the financial sectors and the real sectors world-wide, and then an attempt is made to highlight the propagation mechanism of infective contagion. Theoretical structures of such interconnected are showcased through various analytical vehicles. The indices of sensitivities and dispersions are measured in mathematical terms, and in that sense a new analytical framework is presented. However, empirical evaluations of the propagation mechanism remain unfinished because of the dearth of data